Determining extent of COVID-19 pneumonia on CT based on biological variables. (December 2020) - Tordjman, Mickael; Mekki, Ahmed; Mali, Rahul D.; Monnier, Hippolyte; Neveu, Sophie; Chassagnon, Guillaume; Mihoubi, Fadila; Carlier, Nicolas; Marey, Jonathan; Fournier, Laure; Carlier, Robert-Yves; Drapé, Jean-Luc; et al.
Abstract: Introduction: Covid-19 pneumonia CT extent correlates well with outcome including mortality. However, CT is not widely available in many countries. This study aimed to explore the relationship between Covid-19 pneumonia CT extent and blood tests variations. The objective was to determine for the biological variables correlating with disease severity the cut-off values showing the best performance to predict the parenchymal extent of the pneumonia. Methods: Bivariate correlations were calculated between biological variables and grade of disease extent on CT. Receiving Operating Characteristic curve analysis determined the best cutoffs for the strongest correlated biological variables. The performance of these variables to predict mild (<10%) or severe pneumonia (>50% of parenchyma involved) was evaluated. Results: Correlations between biological variables and disease extent was evaluated in 168 patients included in this study. LDH, lymphocyte count and CRP showed the strongest correlations (with 0.67, −0.41 and 0.52 correlation coefficient, respectively). Patients were split into a training and a validation cohort according to their centers. If one variable was above/below the following cut-offs, LDH>380, CRP>80 or lymphocyte count <0.8G/L, severe pneumonia extent on CT was detected with 100% sensitivity. Values above/below all three thresholds were denoted in 73% of patients with severe pneumonia extent. The combination of LDH<220 and CRP<22 was associated with mild pneumonia extent (<10%) with specificity of 100%. Discussion: LDH showed the strongest correlation with the extent of Covid-19 pneumonia on CT. Combined with CRP±lymphocyte count, it helps predicting parenchymal extent of the pneumonia when CT scan is not available. Highlights: Patients with mild respiratory symptoms are not necessarily referred for CT when they are diagnosed with SARS-CoV2 infection. Previous studies demonstrated than extent of Covid-19 pneumonia on CT is related to patients' outcome. LDH combined with CRP and lymphocyte count, help predicting parenchymal extent of the pneumonia when CT-scan is not available.